Interactive Storytelling with Hand Puppets for Improving Speaking Skills in Children with Speech Delay - Wahyuni, Wahyuni; Sukinah, Sukinah (Papanda Publisher, 2025)
Speech delay affects 3-20% of early childhood populations globally, impacting communication abilities, social interaction, and academic readiness. Hand puppet storytelling represents a potentially effective intervention approach combining narrative engagement with interactive visual elements to stimulate verbal responses in affected children. This classroom action research employed the Kemmis and McTaggart model across two intervention cycles. One 5-year-old participant with identified speech delay received hand puppet storytelling sessions twice weekly over six weeks. Data collection utilized structured observation checklists assessing seven speaking skill indicators, semi-structured teacher interviews, and anecdotal records. Quantitative analysis calculated percentage improvements, while qualitative data underwent thematic analysis. Significant speaking skill improvements were demonstrated from baseline assessment (28.57%) to post-intervention (62.5%), representing a 33.93% increase that exceeded the predetermined 30% success criterion. Five out of seven assessment indicators achieved